Role of patient-, tumor- and systemic inflammatory response–related factors in predicting survival of patients with node-negative gastric cancer. Issue 6 (May 2017) - Qu, Jinglei; Qu, Xiujuan; Li, Zhi; Zhang, Jingdong; Teng, Yuee; Jin, Bo; Zhao, Mingfang; Yu, Ping; Wang, Zhenning; Liu, Yunpeng
It is currently unclear as to which patients with node-negative gastric cancer can benefit from adjuvant chemotherapy. This study aimed to develop a prognostic model based on patient-, tumor-, and host-related factors to stratify high-risk patients eligible for adjuvant therapy. Correlations of clinicopathological and hematological features with overall survival were analyzed using a Cox model. A score to identify risk classes was derived from hazard ratios in multivariate analysis. In all, 436 patients with node-negative gastric cancer (stage pT1–4aN0M0) were analyzed in this study. Multivariate analysis showed that age, depth of invasion, and neutrophil–lymphocyte ratio were independent prognostic indicators of overall survival, and a prognostic model was developed using these significant factors. Patients were stratified into three risk groups with significant differences in the 3-year survival rates (98.5%, 91.6%, and 70.7%, respectively; p < 0.001) according to their scores. The prognostic model improved the predictive accuracy of postoperative 3-year survival rate by 7% when compared with the pathological T stage. A model based on age, depth of invasion, and neutrophil–lymphocyte ratio is more effective than traditional staging systems in predicting the prognosis of node-negative gastric cancer. High-risk patients could be considered for adjuvant therapy.